Escherichia coli in the Niger River: Links to environmental variables and anthropogenic activities in Niamey city, Niger - Moussa Boubacar Moussa; Amadou Abdourhamane Touré; Bruno Lartiges; Laurent Kergoat; Elodie Robert; Aliko Mamane; Olivier Ribolzi; Emma Rochelle-Newall; Manuela Grippa (Journal of Hydrology: Regional Studies)
Study region: Middle Niger River, upstream to downstream of Niamey city, Sahel, West Africa. Study focus: Understanding surface water pollution dynamics and identifying its main drivers is particularly important in regions where surface waters are largely used without proper treatment. This study is focused on the Niger River water and assesses E. coli numbers, and physicochemical parameters upstream and downstream of Niamey. Data collected over three years, supplemented by occasional campaigns, aimed to determine the spatial and temporal variability of water quality. New hydrological insights for the region: SPM and E. coli showed high values during the rainy season, peaking before the Red flood. E. coli increased from the first rainfall events in Niamey with a peak occurring before SPM peak. Distinct sources play an important role on their seasonal dynamics; E. coli mainly originates from urban areas along the Niger River, while SPM comes from right-hand tributaries upstream of Niamey. Downstream of Niamey, E. coli were significantly higher than upstream, highlighting the city's substantial contribution to fecal contamination through wastewater discharges, particularly on the left bank. No significant differences between upstream and downstream were observed in the other physicochemical parameters analyzed. Considering spatial distribution in E. coli sources and environmental parameters such as rainfall and SPM is of major and global importance for understanding and addressing fecal contamination in urban environments.